Effects of progesterone and estradiol on the inflammatory and apoptotic markers of ovariectomized rats challenged with acute septic systemic inflammation - Sinan Subhi Farhan, Samir Saad Mahgoub, Saad Abdulrahman Hussain (Journal of Applied Pharmaceutical Science, 2019)
The inflammatory responses during septic inflammation were affected by the differential role of progesterone and estrogen that demonstrated pro-inflammatory and anti-inflammatory roles. This study was designed to evaluate the differential effects of estradiol and progesterone supplementation on the inflammatory and apoptotic responses in an ovariectomized (OVX) rat model of acute systemic septic inflammation (SSI). This study was conducted on 60 female Wistar rats. 40 mg/kg estradiol and 5 mg/kg progesterone were given subcutaneous (s.c.) to OVX rats, after the induction of SSI through caecum puncture with a 21-gauge needle. Serum levels of tumor necrosis factor-α (TNF-α), C-reactive protein (CRP), Alanine transaminase (ALT), estradiol, and progesterone were evaluated; additionally, Inducible nitric oxide synthase (iNOS), Cyclooxygenase (COX)-II, and caspase-3 were evacuated in liver tissue homogenates using the Enzyme-linked immunosorbent assay (ELISA) method. In OVX rats challenged with SSI, serum TNF-α, CRP, and ALT levels were significantly increased associated with a decrease in serum estradiol levels. They also showed overexpression of iNOS and increased the activity of COX-II and caspase-3 in the liver compared to non-OVX rats subjected to SSI. Supplementation with estradiol significantly decreases all serum and liver tissue markers of inflammation and decreased apoptosis. In contrast, in OVX rats supplemented with progesterone, SSI resulted in a significant increase in the studied markers. In conclusion, the supplementation of estradiol in OVX rats challenged with SSI significantly attenuated the systemic and liver inflammatory and apoptotic markers. Meanwhile, the supplementation with progesterone exacerbates the effects of the inflammatory markers and increases the tendency of apoptosis in the liver tissue.
Keywords: Septic systemic inflammation, liver, estradiol, progesterone, apoptosis.